The psychology of B.F. Skinner - O'Donohue, William T. (Sage, 2001)
Behaviorists, or more precisely Skinnerians, commonly consider Skinner's work to have been misrepresented, misunderstood, and to some extent defamed. In this book, the author clarifies the work of B F Skinner, and puts it into historical and philosophical context. Though not a biography, the book discusses Skinner himself, in brief. But the bulk of the book illuminates Skinner's contributions to psychology, his philosophy of science, his experimental research program (logical positivism) and the behavioral principles that emerged from it, and applied aspects of his work. It also rebuts criticism of Skinner's work, including radical behaviorism, and discusses key developments by others that have derived from it.